Problematika Fungsi Kerapatan Adat Nagari (KAN) Dalam Penyelenggaraan Pemerintahan Nagari Sebagai Satuan Pemerintahan Terendah yang Menganut Otonomi Asli - Setiawan, Dian Bakti; Alsyam, Alsyam (Faculty of Law, Andalas University, 2025)
The regulation concerning the functions of the Kerapatan Adat Nagari (KAN) in the Regional Regulation of West Sumatra Province presents several issues. On one hand, this regulation aims to strengthen the role of KAN by expanding its membership composition to ensure broader representation. However, on the other hand, this expansion becomes counterproductive as it leads to uncertainty regarding the number of KAN members. A fixed number of members is crucial for the validity of decision-making processes and the legitimacy of the decisions made. Similarly, the authority granted to KAN to formulate Peraturan Nagari (Perna) also raises concerns. Since Perna serves as a primary instrument in the implementation of Nagari autonomy, granting KAN the authority to establish Perna could be seen as an effort to reinforce KAN as a customary institution. However, it could also be viewed as a restriction of customary jurisdiction, as Peraturan Nagari must inherently take the form of written law. Furthermore, if Peraturan Nagari—except for the Nagari Revenue and Expenditure Budget (APB-Nag)—were to be established in an unwritten form, it would create difficulties in Nagari governance, as written regulations provide greater legal certainty and serve as essential documents for various administrative purposes. Therefore, KAN membership should ideally be limited to ninik mamak (customary elders), and its functions should be restricted to formulating policies within the domain of customary law. Additionally, KAN should be responsible for proposing recommendations for Perna to the Badan Permusyawaratan Nagari (Nagari Consultative Body) whenever certain matters are deemed significant enough to be formalized into Peraturan Nagari.